Efikasi Diri Merupakan Faktor Yang Berhubungan Dengan Resiliensi Keluarga Yang Memiliki Remaja Dengan Gangguan Jiwa Berat - Barimbing, Maryati Agustina (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Severe mental disorders in adolescents have an negative impact on sufferers and their families. This negative impact can be prevented and overcome when families have resilience, that is the ability to survive and fight the stressors. Factor related to family resilience based on the theory of "Resilience" according to Haase & Peterson is self-efficacy. The aim of the study was to analyze the relationship between self efficacy and resilience of families with adolescent severe mental disorders. This study used an correlation method with a cross sectional approach. The study was conducted on 60 families of adolescents with severe mental disorders who were selected by purposive sampling technique. The study was conducted at Dr. Radjiman Wediodiningrat Lawang Mental Hospital. The bivariate analysis by Pearson correlation test showed that there was a significant relationship between self-efficacy with family resilience (p = 0,000, r = 687). The conclusion obtained is that family resilience can be strengthened by increasing self efficacy. From the results of this study it is expected that families can increase their resilience while caring for family members with mental disorders and for nurses can convey related resilience in nursing care to people with mental disorders and their families.